2015
DOI: 10.1109/tthz.2015.2428619
|View full text |Cite
|
Sign up to set email alerts
|

Counterbalanced Effect of Surface Trap and Auger Recombination on the Transverse Terahertz Carrier Dynamics in Silicon Nanowires

Abstract: The surface-trap mediated carrier recombination is a crucial feature in characterizing the optoelectronic properties of nanowires (NWs). Due to the one-dimensional characteristics, the photoexcited carriers experiences multiple carrier interactions in the transverse direction such that strong carrier-carrier interactions are expected to play an important role in the NW carrier recombination. Here, using ultrafast optical-pump and terahertzprobe spectroscopy, we show that the Auger scattering significantly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Conversely, the slope of ΔA changed from 1 to 0.5 near the 0.4‐mJ/cm 2 fluence of the pump wavelength at 532 nm. Since the pump pulse at 532 nm possessed an energy of 2.33 eV that is higher than the Si indirect bandgap ( E g = ∼1.12 eV), the excess energy of conduction band carriers in a solar cell was thermalized through electron‐electron or electron‐phonon scattering . The initial fast carrier‐carrier scattering process beyond the probe time resolution of TDRS (approximately 40 ns) led to nonradiative carrier recombination and suppressed the increase of ΔA at a high pump fluence.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the slope of ΔA changed from 1 to 0.5 near the 0.4‐mJ/cm 2 fluence of the pump wavelength at 532 nm. Since the pump pulse at 532 nm possessed an energy of 2.33 eV that is higher than the Si indirect bandgap ( E g = ∼1.12 eV), the excess energy of conduction band carriers in a solar cell was thermalized through electron‐electron or electron‐phonon scattering . The initial fast carrier‐carrier scattering process beyond the probe time resolution of TDRS (approximately 40 ns) led to nonradiative carrier recombination and suppressed the increase of ΔA at a high pump fluence.…”
Section: Resultsmentioning
confidence: 99%
“…This is a method to fabricate nanostructures of vertically-aligned structures by patterning metal on the substrate. This makes it possible to fabricate well-aligned vertical nanostructures according to patterned metals, but for fabrication of laterally-aligned silicon-nanowire arrays, the aligned structures can be deformed during substrate transfer [19], or the separation of nanostructures from the substrate can be difficult [20]. The Si/SiGe epitaxy method has also been reported to fabricate the nanowire [21].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of SiNWs with a planar circuitry provides a range of hybrid electronic systems that function as FETs, solar cells, biochemical sensors, and Esaki diodes . In addition, SiNWs have demonstrated reconfigurable light–matter interactions, as the large surface‐to‐volume ratio with respect to bulk Si counterparts effectively increases the absorption cross‐section . Previous studies have shown that an efficient light detection using SiNWs requires p – i – n junctions; the engineering of co‐axial geometry produces functional optoelectronics such as photovoltaic‐based light sensors and logic gates …”
mentioning
confidence: 99%